Autonomy as a psychological pathway linking family quality of life to resilience - Rita Eka Izzaty; Yulia Ayriza; Banyu Wicaksono; Norzarina Mohd Zaharim; Intan Hashimah Mohd Hashim (University of Muhammadiyah Malang, 2026)
Adolescents who cope poorly with developmental challenges are at risk of developing psychological problems. Family quality of life and autonomy may function as protective factors that strengthen resilience. This study examined autonomy as a mediator of the association between family quality of life and resilience among Indonesian and Malaysian adolescents. Participants were recruited using purposive sampling and completed the Brief Resilience Scale, Adolescent Autonomy Scale, and Beach Center Family Quality of Life Scale through an online survey. The findings showed that autonomy mediated the association between family quality of life and resilience in both samples. The mediation was partial among Indonesian adolescents, whereas an indirect-only association was observed among Malaysian adolescents. However, differences in the direct pathways across countries could not be established because measurement invariance was not supported. These findings highlight autonomy as a potential mechanism linking family quality of life with adolescent resilience, while emphasizing the importance of measurement invariance for valid cross-national comparisons.